Involvement of mTOR in CXCL12 mediated T cell signaling and migration. - Rachel Munk; Paritosh Ghosh; Manik C Ghosh; Takeshi Saito; Mai Xu; Arnell Carter; Fred Indig; Dennis D Taub; Dan L Longo (PLoS ONE, 2011)
CXCL12 is a pleiotropic chemokine involved in multiple different processes such as immune regulation, inflammatory responses, and cancer development. CXCL12 is also a potent chemokine involved in chemoattraction of T cells to the site of infection or inflammation. Mammalian target of rapamycin (mTOR) is a serine-threonine kinase that modulates different cellular processes, such as metabolism, nutrient sensing, protein translation, and cell growth. The role of mTOR in CXCL12-mediated resting T cell migration has yet to be elucidated.Rapamycin, an inhibitor of mTOR, significantly inhibits CXCL12 mediated migration of both primary human resting T cells and human T cell leukemia cell line CEM. p70(S6K1), an effector molecule of mTOR signaling pathway, was knocked down by shRNA in CEM cells using a lentiviral gene transfer system. Using p70(S6K1) knock down cells, we demonstrate the role of mTOR signaling in T cell migration both in vitro and in vivo.Our data demonstrate a new role for mTOR in CXCL12-induced T cell migration, and enrich the current knowledge regarding the clinical use of rapamycin.